The Existence Of The Kabuyutan Cultural Heritage Site And Its Influence On The Socio-Economic Conditions Of The Surrounding Communities - Neneng Nenih; Upi Supriatna; Dini Sukmawati (Jurnal Pendidikan Ilmu Sosial, 2024)
The existence of the Kabuyutan Cultural Heritage Site in Pasrijambu Village, Pasirjambu District, Bandung Regency has become a religious tourism attraction. The aim of the research carried out was to analyze how the existence of the Kabutuan Cultural Heritage Site affects the socio-economic conditions of the surrounding community. The method used in this research is a descriptive research method using questionnaire techniques and interviews. Meanwhile, the research population was 362 families with a sampling technique using random sampling with a total of 60 respondents taken from 15% of the population, namely 362 people which resulted in 60 respondents. The research results show that the Kabuyutan Cultural Heritage Site influences the socio-economic conditions of the community because even though the majority of the surrounding community have their livelihoods in the agricultural sector, with the presence of tourists/pilgrims the community provides services to meet their needs. The results of this research certainly provide opportunities for local communities to develop small and medium businesses.